Potential And Carrying Capacity of Tourism Area in Onanbalu Beach, Bokonusan Village, Semau Island, Kupang District - Suprabadevi Ayumayasari Saraswati; Fandrianus Dhena Manu; Alexander Leonidas Kangkan (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2023)
This research was conducted to know the physical potential of Onanbalu Beach and what attractions could be developed as well as the carrying capacity of the area. The research method used is a scoring method based on the value of tourism suitability and analysis of the carrying capacity of the area. The research shows that: (1) The physical potential of Onanbalu beach consists of a beach width of 1.77-2 m; The type of beach is white sand, rocky and rocky; The width of the beach is 40.30-58 m; The basic material of the waters is rocky sand; Current speed is 0.19-0.27 m/s; The slope of the beach is 7-10°; The brightness of the waters is 3 m; Closure of coastal land in the form of trees, thickets, and settlements; Dangerous biota in the form of sea urchins; Availability of fresh water, namely 1-2.21 km, (2) Attractions that are suitable for development on Onanbalu beach, namely beach recreation, sunbathing, swimming, beach volleyball, and boating as well as the carrying capacity of the area carried out on Onanbalu beach, which can accommodate 14,833 people every day, with a total tourist area of 47.2 Ha. The area of Onanbalu Beach which is utilized for all activities is 27.78 Ha.